The flaring efficiency of the Profile and Protaper on resin simulated root canals (Mustansiria Dental Journal, 2024)
Forty resin simulated root canals with standardized curvature prepared for thisstudy, divided into four groups ten canals for each group. Thirty canals were preparedwith rotary endodontic instruments, profile 04, profile 04, 06 and protaper, ten canalsfor each type, with slow speed contra angle hand piece (300 rpm) using crown — downtechnique the other l0 canals were prepared with stainless steel k-flexo handinstrument using step — back technique. The total time required for preparation wascalculated. The resin blocks were scanned; the pre-instrumented and post -instrumented images were stored in the computer and superimposed for twodimensional evaluation of canals preparation using Adobe photoshope 8.0 and Coreldraw 9. For the coronal portion the amount of canal substance removed wascalculated at 7mm, 9mm, llmm levels from the working length. For the apicalcurvature the centering ratio was calculated at 2mm and 4mm level from the workinglength. The results showed that the amount of canal substance removed from thecoronal portion by protaper was statistically higher than other groups with statisticallyless ability to stay center in the canal than profile rotary instruments but more abilityto preserve apical curvature than k-flexo hand instruments with less time required forpreparation. K-flexo files showed statistically less amount of canal substance removalat coronal portion and statistically higher centering ratio than other groups, andrequire more time for canals preparation .